Liver FOXP3 and PD1/PDL1 Expression is Down-Regulated in Chronic HBV Hepatitis on Maintained Remission Related to the Degree of Inflammation - Germanidis, Georgios; Argentou, Nikoletta; Hytiroglou, Prodromos; Vassiliadis, Themistoklis; Patsiaoura, Kalliopi; Germenis, Anastasios E.; Speletas, Matthaios (Frontiers in Immunology, 2013)
Background & aim: T-cell expression of PD1 and inhibition of T effector cells by Foxp3+-T regulatory cells are among the most powerful mechanisms for achieving a balanced immune response. Our aim was to investigate, how liver FOXP3 and PD1/PDL1 expression is regulated in chronic HBV hepatitis (CHB) on maintained long-term remission in comparison with active disease, and whether they are correlated to the expression of pro- and anti-inflammatory cytokines and apoptosis mediators, along with the degree of histological inflammation and markers of T-cell effector restoration. Methods: Fifty-three HBeAg-negative CHB patients with both active (30) and completely remitted disease on long-term antiviral treatment (23) and 4 controls (submitted to liver biopsy due to a mild increase of aminotransferases but without liver necroinflammatory and architecture changes) were enrolled in the study. Liver mRNA levels of immunoregulatory genes (FOXP3, IL10, TGFB1, and those of PD1/PDL1/PDL2 pathway), major apoptosis mediators (FAS, FASL, TNFA, TRAIL), cytokines of effector T-cell restoration (IL2, IFNG), and those of IL1B, CD4 and CD8, were evaluated by qRT-PCR and were correlated with each other, along with the intensity of liver inflammation and fibrosis staging. The expression and localization of FOXP3, PD1, PDL1, CD4, and CD8 were also assessed by immunohistochemistry. Results: The expression of FOXP3, IL10, TGFB1, PD1, PDL1, FASL, and CD8 was significantly down-regulated in the remission state. In contrast, liver expression of IL2 and IFNG, along with CD4, IL1B, TNFA and FAS did not change significantly. Moreover, FOXP3, PD1, PDL1, and CD8 transcripts were positively correlated to the intensity of liver inflammation. Conclusion: Our data indicate that in the CHB disease model, the immunosuppressive liver environment is down-regulated in the maintained on-treatment long-term remission state and correlates with the intensity of liver inflammation, but not liver T-cell restoration.